O sofrimento psíquico na infância: uma análise psicanalítica sobre o fenômeno do suicídio - Guimarães, Karoline da Costa (Universidade Federal do Tocantins, 2024)
The present work consists of an exploratory and descriptive study on psychological suffering in childhood in a psychoanalytic analysis of the phenomenon of suicide. Thus, the analysis of the material studied showed that suicide for psychoanalysis is understood as a way out, an action, an outcome of unbearable suffering present in society, and which becomes evident every year. Some of the materials analyzed were Freud's psychoanalytic works, as well as scientific articles, books, dissertations and theses that pointed out many risk factors that trigger the problem. This study is divided into three chapters, namely: Demystifying childhood; The development of the conception of death; Child suicide: some contributions from Freud. It is also observed that due to the lack of resources to deal with daily life, some children develop a feeling of inferiority that can later lead to a loss of attachment to life. Therefore, it is also necessary for the knowledge and identification of more risk and protective factors against child suicide to be based on theories capable of bringing a more comprehensive understanding of the subject.